Editorial - Chief Editor (Indian Journal of Extension Education, 2022)
World Science Day for Peace and Development focused attention on the understanding how societies are contending with the challenges and threats of a world in which the frequency and severity of shocks and conflicts continues to grow. The studies through robust methodologies can trace out the impacts of various shocks and crises afflicting the world today, as well as trace out policy solutions that can address them and improve the lives of the rural poor, also, can expand the body of scientific evidence to promote peace and development. New skills are needed to deal with challenges posed by COVID-19 pandemic which forced innovation within extension organizations. Although digital literacy is critical but individuals and organizations will need skills for partnering and building alliances, as well as for coordination and joint monitoring and evaluation as such development actors need to ensure system-level capacities. It’s my privilege to present the current issue (January- March, 2023) containing 38 manuscripts including 4 research tools, 9 research notes and 25 full length research papers from cross sectional authors and content. The measuring tools included; attitude scale towards conservation agricultural practices; sustainability of rice-wheat cropping system; social cohesiveness and one knowledge test on Rashtriya Krishi Vikas Yojana. The manuscripts on constraint analysis of ericulture, turmeric production, agroforestry practices and farm pond; knowledge analysis of IPM and various dimensions of Krishi Bhagya Yojane; communication related studies like; social Network analysis for technology adoption, effectiveness of educational module, information networks analysis, content analysis of newspaper, OTT platforms study, MobileApp utilization pattern and credibility analysis of information sources; adoption studies on artificial insemination, climate resilient agricultural technologies, sustainable livelihood security of integrated farming systems, soil health card scheme , livelihood security of households, intercropping and technological gap between tribal pineapple growers; economic analysis of lac production, trade between India and European Union, potato , composition of agricultural household’s income, mushroom enterprises and e-NAM facilities and services and some miscellaneous studies on water user associations, research productivity, readiness for organic farming etc. were included. The data is regularly being fed to international indexing agencies leading to indexing of Indian Journal of Extension Education at Index Copernicus International Journal Master list, CAB International; ICI; BASE; Googkle scholar; Scilit; Semantic Scholar; WorldCat; Science gate; Agricultural Science and Technology Information data base of FAO and Crossref. From June 2023, as per changed policy, all the journals indexed in Web of Science (WoS) will get Impact Factors whereas earlier only the core collection of Science Citation Index was getting the Impact Factor (JIF) published in Journal Citation Report (JCR). As such it has become more looked-for to get the journal indexed in WoS for which we all have to work harder. I extend my sincere thanks to all the authors for making valuable contributions. I also extend sincere thanks to all the expert members in the editorial board for their painstaking efforts. The reviewing contributions by Dr. Himanshu K. De, Dr. Rajeev Bairathi, Dr. Souvik Ghosh, Dr. Mahesh Chandra, Dr. P.K. Tiwari, Dr. L. K. Tyagi, Dr. Raju, Dr. N. V. Kumbhare and many other are sincerely acknowledged. I extend my sincere thanks to all the authors for making valuable contributions. The support extended by Executive Council is duly acknowledged. Special thanks are extended to the President, ISEE; Dr. U.S. Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bringing out this issue. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters. (Manjeet Singh Nain)